1998
DOI: 10.1159/000029026
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in Children of Patients with Panic Disorder or Animal Phobia

Abstract: Several studies reveal a heightened risk for anxiety and other mental disorders in the offspring of patients with panic disorder and other anxiety disorders. Data on the specific type of transmitted disorders, however, are inconsistent. We investigated the specificity of the relationship between parents’ and children’s psychopathology. We assessed current and past mental disorders in 5- to 15-year-old children of patients with panic disorder (CPAN, n = 34), children of parents with no diagnosis of a mental dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 31 publications
3
23
0
1
Order By: Relevance
“…separation anxiety disorder, generalized anxiety disorder, social anxiety disorder). These results are reported in detail in Unnewehr et al [39] .…”
Section: Childrensupporting
confidence: 71%
“…separation anxiety disorder, generalized anxiety disorder, social anxiety disorder). These results are reported in detail in Unnewehr et al [39] .…”
Section: Childrensupporting
confidence: 71%
“…In the present study, the mean score obtained by children with separation anxiety on items of SCARED was relatively low (2.4=1.7). Although some studies have found an excess of separation anxiety in offspring of adult panic disorder subjects [Unnewehr et al, 1998], others have questioned this association between separation anxiety and adult panic disorder [Biederman et al, 2001]. Yet, another reason for a lack of relationship between heart rate variability and childhood anxiety symptoms could be due to the relatively high cholinergic modulation of cardiac activity among children [Yeragani et al, 1994a], but one could debate that this is more of a reason to find significant differences in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a higher rate of separation anxiety disorder was observed among children of patients with panic disorder as compared to children of parents with animal phobia who had a higher rate of phobic disorders [Unnewehr et al, 1998]. In another study of high-risk children, Biederman et al [2001] reported that parental panic disorder regardless of comorbidity with major depression conferred a greater risk for panic disorder and agoraphobia in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Aufgrund der familiären Häufung von Ängsten [Überblick bei Schneider, 1995;Unnewehr et al, 1998], ist es für eine erfolgreiche Behandlung des Kindes oft sinnvoll, die Eltern in die Angstbehandlung einzubeziehen. Windheuser [1977] und Barrett et al [1996] …”
Section: ) Einbezug Der Elternunclassified